2001
DOI: 10.1103/physrevb.63.214405
|View full text |Cite
|
Sign up to set email alerts
|

MnK-edge XANES studies ofLa1xAxMnO3

Abstract: We present Mn K-edge x-ray absorption near-edge structure ͑XANES͒ data for a number of manganite systems as a function of temperature. The 1s absorption edge for the Ca-substituted samples is very sharp, almost featureless, and shifts uniformly upwards with increasing Ca content. The interpretation of this result is controversial because the lack of structure appears difficult to reconcile with a mixture of Mn ϩ3 and Mn ϩ4 ions or with several different Mn-O bond lengths at high T. We propose a possible soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
69
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 54 publications
8
69
0
Order By: Relevance
“…In Ln materials, the strong localization of the f electrons guarantees a large Up f , thereby enabling a split peak in all known Ln intermediate valence materials at the Ln L 3 edge. In contrast, this splitting condition is typically not met in transition metal systems, and no split peaks are observed (energy shifts are observed instead) [49]. Actinides can potentially exhibit either kind of behavior.…”
Section: Discussionmentioning
confidence: 97%
“…In Ln materials, the strong localization of the f electrons guarantees a large Up f , thereby enabling a split peak in all known Ln intermediate valence materials at the Ln L 3 edge. In contrast, this splitting condition is typically not met in transition metal systems, and no split peaks are observed (energy shifts are observed instead) [49]. Actinides can potentially exhibit either kind of behavior.…”
Section: Discussionmentioning
confidence: 97%
“…It was suggested that the intensity of the peak B is proportional to a displacement of Ti atoms from the center of the TiO 6 octahedra [30] but inversely related to the Ti-O bond length. The peak C is a 4p-related "shape resonance" in the continuum part of the spectrum and the peak D is attributed to more delocalized states [34,35]. The XANES spectra show almost no edge shift as a function of x but its intensity and shape change systematically with x.…”
Section: Xafs Studymentioning
confidence: 97%
“…The sample was mounted in an evacuated variable temperature Displex cryostat equipped with a Be dome. In this experiment, we probe the absorption K edge of Mn, corresponding to the allowed electric dipole transition from the 1s core level to unoccupied 4p states [18][19][20]. The light absorption, normalized to the incident photon flux, was measured in the fluorescence mode using the Mn K α line at 5899 eV using a Si drift x-ray detector spectrometer.…”
mentioning
confidence: 99%